An MRI-Compatible Foot-Sole Stimulation System Enabling Characterization of the Brain Response to Walking-Related Tactile Stimuli - Zhang, Tingwei; Zhang, Kai; Zhou, Junhong; Chai, Yufeng; Long, Yunfei; Wang, Xiaoying; Manor, Brad; Zhang, Jue; Fang, Jing (Frontiers in Neuroscience, 2019)
Foot-sole somatosensory impairment is a main contributor to balance decline and falls in aging and disease. The cortical networks involved in walking-related foot sole somatosensation, however, remain poorly understood. We thus created and tested a novel MRI-compatible device to enable study of the cortical response to pressure stimuli applied to the foot sole that mimic those stimuli experienced when walking. The device consists of a dual-drive stimulator equipped with two pneumatic cylinders, which are separately programed to apply pressure waveforms to the entire foot sole. In a sample of nine healthy younger adults, the pressure curve applied to the foot sole closely correlated with that experienced during over ground walking (r = 0.811 ± 0.043, P < 0.01). MRI compatibility testing indicated that the device has no or negligible impact on MR image quality. Gradient-recalled echo-planar images of nine healthy young adults using a block-designed 3.5-min walking-related stimulation revealed significant activation within the supplementary motor area, supramarginal gyrus, paracingulate gyri, insula, precentral gyrus, middle temporal gyrus, and hippocampus (uncorrected P < 0.001, k ≥ 10). Together, these results indicate that this stimulation system is MRI-compatible and capable of mimicking walking-related pressure waveforms on foot sole. It may thus be used as a research tool to identify cortical targets for interventions (e.g., non-invasive brain stimulation) aimed at enhancing this important source of input to the locomotor control system.